Sports Club for Health movement: terminology and definitions - Pedišić Željko; Podnar Hrvoje; Radman Ivan; Oja Pekka; Rakovac Marija; Benedičič Tomat Saška; Bělka Jan; Broms Lovisa; Chaplais Elodie; Chen Si-Tong; De Grauwe Guy; Em Sowannry; et al. (University of Zagreb, Faculty of Kinesiology, 2025)
The Sports Club for Health (SCforH) movement has been growing and advancing since its establishment in 2008. In parallel with the constantly growing team and scope of SCforH activities, there has also been an increase in the number of specialised terms used in our verbal communication, written correspondence, and publications. To help standardise the use of such specialised terms, as part of the SCforH 2015-17 project, through a range of discussions within the project team and consultations with project partners, we reached a consensus on the classification and definitions of physical activities. However, some of the specialised terms used in SCforH-related are also related to the structure, activities, outputs, and partners of the SCforH movement, as well as to the structure of the European and national sports systems. Therefore, as part of the SCforH 2020-22 project, we developed this comprehensive glossary of SCforH-related terms with the aim to facilitate their conceptual understanding and standardised use. The terms were identified by searching through the published documents and web content identified in a systematic scoping review of SCforH-related publications. The draft list of terms and their definitions were reviewed by 10 SCforH experts. A revised list was then reviewed and approved by 32 SCforH experts. Overall, we listed and defined 46 specialised SCforH-related terms. The glossary may help new members of the SCforH consortium to gain understanding of the common SCforH terminology and provide clarity to the readers of our publications. It may also facilitate a standardised use of the terms in the SCforH context. Where suitable, the members of the SCforH consortium should be encouraged to use these definitions, to improve the clarity of future SCforH communications.
Sports Club for Health (SCforH) movement in the European Union.